Hardware Acceleration of Video Edge Detection with Hight Level Synthesis on the Xilinx Zynq Platform - Saidani, T.; Ghodhbani, R. (Engineering, Technology & Applied Science Research, 2022)
The study conducted in the current paper consists of validating an original design flow for the rapid prototyping of real-time image and video processing applications on FPGAs. A video application for edge detection with Simulink HDL coder and Vivado High-Level Synthesis (HLS) has been designed as if the code was going to be executed on a conventional processor. The developed tools will automatically translate the code into VHDL hardware language using an advanced compilation technique. This amounts to embedding processors on Xilinx Zynq-7000 System on-Chip (SoC) device in an optimal manner. This automated hardware design flow reduces the time to create a prototype since only the high-level description is required. The design of the video edge detection system is implemented on Xilinx Zynq-7000 platform. The result of the implementation gave effective resource utilization and a good frame rate (95 FPS) under 170MHz frequency.